(untitled) (Medico Legal Update, 2020)
Purpose: This study is a descriptive survey to investigate the relationship between health promoting behaviors and self-efficacy, health perception, social support and perceived disability and to identify factors affecting health promoting behaviors among nursing students. Method: With the permission of the Education Committee of the Department of a University, 249 nursing college students explained the purpose and method of research and collected data with written consent. The data were analyzed by the t-test, ANOVA and Pearson’s correlation and Stepwise Multiple Regression using the SPSS 24.0 program. Results: The health promoting behaviors of the subjects were a positive correlation at the statically significant level at the self-efficacy (r=.73, p<.001), health perception (r=.50, p<.001), Social support (r=.62, p<.001) and a negative correlation at the perceived disability (r=-.29 p<.001). Regression analysis showed that health condition (? =-.144, p <.001), health concern (?=-.147 p<.001), self-efficacy (?=.523, p<.001) and social support (?=.199, p<.001) explained 62.0% of health promoting behaviors and health conditions, health concern, self-efficacy and social support were the main factors influencing health promoting behaviors of nursing student. Conclusion: Through the result of this study, it is necessary to develop programs that allow nursing students to observe their health conditions and raise their interest in health and promote self-efficacy and social support.